From Proclamation to Dialogue: Reconstructing the Cross-Cultural Mission of Christianity in Christian Religious Education - Rependi Sianturi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study explores how to rebuild cross-cultural Christian missions in Indonesia from a monologic proclamation paradigm to a dialogic approach. This study uses a qualitative approach with a review of the latest theological, pedagogical, and social literature. It starts from the reality of religious and cultural pluralism and the sensitivity of the issue of mission in public spaces. The analysis shows that the one-way proclamation paradigm also keeps stereotypes alive, makes people resistant to Christianity, and makes it harder for students to have conversations. This article suggests a framework for Christian Religious Education (CRE) principles that is based on God's mission, incarnational, dialogical, and focused on restoring social relationships. It does this by combining the ideas of missio Dei, interkultural mission, dialogical communication, and social reconciliation.